2020
DOI: 10.1002/etc.4883
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Reliability of bio‐met for Determining Compliance with Environmental Quality Standards for Metals in Europe

Abstract: The importance of considering the bioavailability of metals in understanding and assessing their toxicity in freshwaters has been recognized for many years. Currently, biotic ligand models (BLMs) are being applied for the derivation and implementation of environmental quality standards (EQS) for metals under the Water Framework Directive in Europe. bio-met is a simplified tool that was developed for implementing bioavailability-based EQS for metals in European freshwaters. We demonstrate the reliability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 61 publications
(118 reference statements)
0
14
0
Order By: Relevance
“…Simple, user‐friendly tools are available for performing assessments of Ni bioavailability such as bio‐met. Bio‐met has been demonstrated to provide reliable predictions (Peters et al, 2020) of the local bioavailable Ni concentration and the local HC5 value based on the dissolved Ni concentration from data for the local water chemistry conditions (pH, DOC, and Ca). If bioavailability is not considered, it is possible to identify some of the sites at which there is very low potential risk due to Ni, but it is not possible to reliably estimate RQs for sites at which dissolved Ni exposures are elevated.…”
Section: Outcomes Of the Deselection Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple, user‐friendly tools are available for performing assessments of Ni bioavailability such as bio‐met. Bio‐met has been demonstrated to provide reliable predictions (Peters et al, 2020) of the local bioavailable Ni concentration and the local HC5 value based on the dissolved Ni concentration from data for the local water chemistry conditions (pH, DOC, and Ca). If bioavailability is not considered, it is possible to identify some of the sites at which there is very low potential risk due to Ni, but it is not possible to reliably estimate RQs for sites at which dissolved Ni exposures are elevated.…”
Section: Outcomes Of the Deselection Approachmentioning
confidence: 99%
“…To assess samples (and sites) while appropriately accounting for Ni bioavailability, bio‐met v5 (bio‐met 2019) was used as it has been demonstrated to provide reliable results that are fully consistent with the Ni EQS (Peters et al, 2020). Any samples with at least one bioavailability parameter (pH, DOC, Ca) missing (Table 1) could not be assessed for bioavailable Ni concentrations and therefore had to be excluded from the assessment to ensure that the EQS is applied in accordance with the way in which it was set (EC, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Plausible explanations to variations in PNEC values in different countries are connected to different water chemistry and hence different bioavailability, as well as different ambient background levels. The Bio-Met tool was recently used to assess differences in bioavailability of Cu in a few European countries (Austria, Belgium, Denmark, France, Germany (River Rhine), Sweden, the Netherlands and the United Kingdom) [30]. The study concluded that freshwaters in Sweden were not among the most sensitive waters in Europe due to high levels of DOC and hence low bioavailability of Cu.…”
Section: Background Concentrations Bioavailability and Organism Sensi...mentioning
confidence: 99%
“…The inclusion of site-specific biological analyses to complement chemical-based assays can preferably be used for improved precision in environmental risk assessment. The reliability of the Bio-Met tool is well proven and established [30]. Validation was performed at pH levels between 6.0 and 8.5 for both Cu and Zn, and for Ca 2+ concentrations between 3.1 and 129.0 mg/L for Cu and between 5.0 and 160.0 mg/L for Zn.…”
Section: Introductionmentioning
confidence: 99%
“…The inset in Figure 1 shows the cumulative frequency distribution of risk characterization ratios for 3537 sites from 18 European countries for which sufficient data were available from between 2018 and 2020 to perform an assessment of Ni bioavailability. This assessment was performed using bio-met, which is reliable and consistent with the EQS (Peters et al, 2020).…”
mentioning
confidence: 99%